2018
DOI: 10.21799/frbp.wp.2018.26
|View full text |Cite
|
Sign up to set email alerts
|

Redefault Risk in the Aftermath of the Mortgage Crisis: Why Did Modifications Improve More Than Self-Cures?

Abstract: This paper examines changes in the redefault rate of mortgages that were selected for modification during 2008-2011, compared with that of similarly situated self-cured mortgages. We find a large decline in the redefault rate of both modified and self-cured mortgages over this period, but the improvement was greatest for modifications. Our analysis has identified several important factors contributing to the greater improvement for modified loans, including an increasing share of principal-reduction modificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 16 publications
2
1
0
Order By: Relevance
“…In all other years in our sample (2011 to 2013), HHF is associated with a 22‐percentage point or 35 percent reduction in default at 36 months. This is similar to other studies that found that the redefault rate of modified loans was lower for newer vintages of modifications, likely due to the economic recovery and also to improvements in program implementation over time (Calem, Jagtiani, & Maingi, 2018). Next, we estimate subsample regressions based on whether or not the original loan was originated prior to or after 2008.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…In all other years in our sample (2011 to 2013), HHF is associated with a 22‐percentage point or 35 percent reduction in default at 36 months. This is similar to other studies that found that the redefault rate of modified loans was lower for newer vintages of modifications, likely due to the economic recovery and also to improvements in program implementation over time (Calem, Jagtiani, & Maingi, 2018). Next, we estimate subsample regressions based on whether or not the original loan was originated prior to or after 2008.…”
Section: Resultssupporting
confidence: 89%
“…Similar to these studies, we observe that the effect sizes of a payment reduction are actually larger for those who are underwater. This complements research finding that mortgage modifications that substantially reduce mortgage payments are most effective at preventing redefault (Calem, Jagtiani, & Maingi, 2018; Ganong & Noel, 2020; Haughwout, Okah, & Tracy, 2016; Scharlemann & Shore, 2016). However, prior studies estimate the effects of permanent reductions in mortgage payments.…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation